Ischemic pre and postconditioning in skeletal muscle injury produced by ischemia and reperfusion in rats - Lintz,José Alves (2013)
PURPOSE: To investigate the protective effects of ischemic pre and postconditioning, as well as the association of both methods, in skeletal muscle injury produced by ischemia and reperfusion in rats. METHODS: An experimental study was designed using 40 Wistar rats divided in four groups (n=10): Control - rats submitted to ischemia for 240 minutes (min) and reperfusion for 60 min; Ischemic preconditioning (Pre) - animals submitted to three cycles of clamping and releasing the aorta for five min before being submitted to the ischemia/reperfusion procedure; Ischemic postconditioning (Post) - rats submitted to three cycles of clamping and releasing the aorta for one min after the 240-minute ischemic phase; Ischemic pre and postconditioning (Pre-post) - animals submitted to the same procedures of Pre and Post groups. Skeletal muscle injury was evaluated by measuring serum levels of aspartate aminotransferase (AST), lactate dehydrogenase (LDH) and creatine phosphokinase (CPK); and muscular levels of malondialdehyde (MDA) and glycogen. RESULTS: AST levels were significantly higher in Pre and Pre-post groups (P<.01). There were no differences in LDH and CPK levels. Muscular MDA levels were similar. Glycogen levels were significantly higher in Pre and Pre-post groups (P<.01). CONCLUSIONS: Both preconditioning and its association with postconditioning had a protective effect by avoiding glycogen depletion in skeletal muscle in rats submitted to ischemia and reperfusion. Association of pre and postconditioning did not show advantage compared to preconditioning alone. Postconditioning alone did not show protective effect.